Pelatihan Penerapan Deep Learning Berbasis Canva dalam Implementasi Kurikulum Merdeka bagi Guru Sekolah Dasar di Kabupaten Buru Selatan - Sriwahyuni, Eka; Sofyan, Abdul; Siregar, Hiba Dertyana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was conducted to address elementary school teachers’ limited understanding of the Deep Learning concept as an approach to meaningful learning within the implementation of the Merdeka Curriculum. This issue arises from insufficient pedagogical knowledge and the lack of practice-based training that supports a shift in the learning paradigm. As a solution, an online participatory workshop was provided for elementary school teachers in South Buru Regency to introduce the principles of Deep Learning and the integration of digital technology, particularly the Canva application. The implementation method included conceptual training, technical practice, as well as mentoring and evaluation through pre-tests and post-tests across five assessment aspects. The results indicated an average improvement of 31.4% across all measured aspects, including understanding of the Deep Learning concept (+30%), its application in the elementary school context (+29%), technical skills in using Canva (+38%), creativity in instructional media design (+28%), and the integration of technology in learning (+32%). These findings demonstrate the effectiveness of online training in enhancing teachers’ competencies and promoting the transformation of learning into a more meaningful, reflective, and contextual process.